Netlet: A simple and versatile network middleware for peer-to-peer application program. (April 2017) - Lyu, Zehua; Tu, Xuping; Pei, Xiaobing; Liang, Hu; Sarem, Mudar
Abstract: Due to the complexity of the Internet, it is often difficult to produce a new and stable program within a short period of time. Taking the popular socket application programming interface for example, there are many details to be dealt with in relation to other common networking issues. This paper introduces a new middleware, called Netlet, which provides an easy programming model while hiding the complexity associated with the communications. By using Netlet, the programmer delivers messages without explicitly setting up or closing the connections even for the Network Address Translation sessions. This consequently allows the users to focus more on the specific applications. It demonstrates that Netlet can be applied to a wide range of Internet applications including latency-sensitive applications and computation and bandwidth intensive applications.